Online Instruction as a Pedagogy: Implications for Higher Education Faculty - Edward L. Meyen (Educational Considerations, 1999)
Because online instruction incorporates instructional design and management, asynchronous learning, the process of communication, technology, and the opportunity for accountability in the teaching/learning process, it can be considered a form of pedagogy.